Pengembangan Modal Sosial Kader Surabaya Hebat untuk Menekan Kenakalan Remaja - Prasetyo, Ratna Azis; Karnaji, Karnaji; Syamsiyah, Nur; Savira, Pingkan Sekar; Mawardi, Rafi Aufa (Jurnal PUBLIQUE, 2025)
Juvenile delinquency remains a persistent issue in major cities, including Surabaya. In response, the Surabaya City Government established a grassroots organization, Kader Surabaya Hebat (KSH), to support community-level monitoring and problem-solving at the sub-district level. This study employed a mixed-methods approach involving 50 KSH cadres in Pradah Kalikendal Sub-district. Data collection consisted of three stages: pre-test and post-test questionnaires to assess cadres’ knowledge of juvenile delinquency, and a focus group discussion (FGD) to explore challenges encountered in the field. The findings indicate that KSH cadres possess moderate to high levels of knowledge regarding juvenile delinquency and are generally well-prepared to perform their roles. However, low levels of trust between the community and KSH cadres emerged as a key challenge. As trust is a central component of social capital, its absence hinders effective collaboration and community development. This study recommends strengthening social capital by improving social relations and fostering trust-building strategies to enhance the effectiveness of KSH cadres in addressing juvenile delinquency.